Effect of selected biocides on microbiologically influenced corrosion caused by Desulfovibrio ferrophilus IS5. Issue 1 (December 2018) - Sharma, Mohita; Liu, Hongwei; Chen, Shiqiang; Cheng, Frank; Voordouw, Gerrit; Gieg, Lisa
Abstract The marine bacterial strainDesulfovibrio ferrophilus IS5, known for its lithotrophic growth ability to use metallic iron as a sole electron donor and for causing corrosion of steel, was used in the current study. Four commonly used biocides in the oil and gas industry, namely tetrakis(hydroxymethyl) phosphonium sulfate (THPS), glutaraldehyde (GLUT), benzalkonium chloride (BAC), and GLUT/BAC were selected to study their efficacy in controlling carbon steel corrosion in the presence of this strain. Incubations containing strain IS5 and low carbon steel coupons were prepared in the presence and absence of the four biocides, and these were monitored using both electrochemical methods (electrochemical impedance spectroscopy, linear polarization resistance and potentiodynamic polarization) and surface analyses (scanning electron microscopy, confocal measurements, optical microscopy, and profilometry) to assess the biofilm/metal interactions. When THPS, BAC, and GLUT/BAC treatments were applied, minimal corrosion was measured by all methods. In contrast, severe pitting was observed in the presence of 50 ppm GLUT, similar to what was observed whenD. ferrophilus IS5 was incubated in the absence of biocide, suggesting that GLUT alone may not be effective in controlling MIC in marine environments. This study also showed that the use of non-destructive electrochemical methods is effective for screening for real time biocide selection and monitoring of the impact of chemicals post-dosage in oil and gas operations.